Implementasi Program Menghafal Al-Qur’an di Sekolah Dasar Islam Terpadu (SDIT) At-Taqwa Tulungagung - M. Asep Fathur Rozi; Ismah Fakhrunnisa (STIT Al Mubarok Bandar Mataram - Lampung Tengah, 2022)
This study aims to determine the implementation of the Al-Qur'an memorization program at At-Taqwa Integrated Islamic Elementary School as well as the supporting and inhibiting factors in the implementation of the Al-Qur'an memorization program. The type of research used is descriptive qualitative, by presenting findings related to the implementation of the tahfidz program in the school. Data collection techniques using interviews, observations and documentation. The informants in this study were school principals, Tahfidz program managers, teachers, and students. In addition to interviews with informants, researchers also collected data through observation and study of data documentation related to information on the implementation of the tahfidz program. The data analysis technique uses Miles and Hubberman analysis, namely interactive data analysis consisting of three activity flows that occur simultaneously, namely: (a) data reduction, (b) data presentation, and (c) conclusion/verification. The results of the study showed that the implementation of the Al-Qur'an memorization program during a pandemic at the At-Taqwa Integrated Islamic Elementary School, the teacher tried to make learning possible without burdening students both through methods and the learning process. Supporting factors in memorizing the Al-Qur'an at At-Taqwa Integrated Islamic Elementary School, namely: the method factors used by the teacher, enthusiasm and motivation among students, support from parents, and a comfortable environment and inhibiting factors in the Al-Qur'an memorization program 'an, namely: the factor of facilities and infrastructure in terms of communication, the factor of students' ability to read the Al-Qur'an, and the factor of the role of parents. The results of the implementation of the Al-Qur'an memorization program during the pandemic at Tepadu At-Taqwa Islamic Elementary School were good, because this program had a positive influence on students with an increase in quality in terms of tajwid and makhorijul letters.